(untitled) (Eurasian Journal of Philology Science and Education, 2023)
The purpose of the research carried out in this article is to reveal the current state of economic consciousness of the Kazakh nation and the potential of the state language in increasing national economic culture. There are no scientific works determining what changes, what transformations have taken place in lexicography of lexical units, characteristic for economic discourse, in the previous researches. The problem of the Kazakh language in economic discourse is now becoming very relevant. The reason is that economic consciousness as an internal part of social consciousness, without the development of the national language, is subject to great obstacles both to the processes of development of the national language, and to the processes of economic progress of society. Such sociolinguistic and linguo-economic studies are necessary in the implementation of language policy and the design of language development programs. The article makes an attempt to reveal the potential of the state language and expansion of the sphere of the state language in the potential business environment, the linguostatistics of terms, words, notions, names with economic semantics were visually shown, also the sociolinguistic research was carried out with the purpose, to provide the concrete ways of solution of their language problems, for scientific consideration of questions, got into public discussion in mass media about the role of language and economy, especially the Kazakh language in business. The research included semi-structured interviews with Kazakh-speaking small business owners and a mass online survey of Kazakh-speaking consumers. Potential consumers of the research are the Language Policy Committee of the Ministry of Education and Science of the Republic of Kazakhstan, Atameken, linguists, sociolinguists, linguoeconomists, masters and doctoral students, as well as politicians and journalists.